2006
DOI: 10.1128/jcm.00377-06
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cariogenic Streptococcus mutans in Extirpated Heart Valve and Atheromatous Plaque Specimens

Abstract: The involvement of oral bacteria in the pathogenesis of cardiovascular diseases has been the focus of attention in many studies, and several periodontal pathogens have been detected in diseased cardiovascular lesions, suggesting relationships between oral microorganisms and cardiovascular diseases. However, no information is available regarding the involvement of cariogenic pathogens such as Streptococcus mutans. The presence of oral streptococcal species and periodontitis-related bacteria in 35 heart valve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
210
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 26 publications
8
210
0
4
Order By: Relevance
“…The detection of S. mutans in specimens taken from patients with IE has been reported by either conventional or molecular techniques (Gauduchon et al, 2001;Nakano et al, 2006;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Since IE is initiated by the colonization of the organism on the ECM of damaged endothelium in heart tissue (Moreillon & Que, 2004), bacterial molecules associated with adhesion to ECM are considered important.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of S. mutans in specimens taken from patients with IE has been reported by either conventional or molecular techniques (Gauduchon et al, 2001;Nakano et al, 2006;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Since IE is initiated by the colonization of the organism on the ECM of damaged endothelium in heart tissue (Moreillon & Que, 2004), bacterial molecules associated with adhesion to ECM are considered important.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have observed that stimulation of either Toll-like receptor (TLR) 2 or TLR4 induces the osteogenic responses characterized by the expression of BMP-2 and ALP, among several other osteogenic biomarkers, in human AVICs (8)(9)(10)(11)(12), leading to the formation of calcification deposits in vitro (11)(12)(13). Moreover, bacteria associated with chronic periodontal infection and bacterial agents have been detected in diseased human aortic valves (14,15), and inoculation of rabbits with oral bacteria induces aortic valve lesions (16). These findings suggest a link between TLRs and CAVD.…”
mentioning
confidence: 99%
“…We have been conducting studies to determine the frequency of detection of oral bacteria in cardiovascular specimens (Nakano et al, 2006a and were interested in the clinical distribution frequency of strains similar to V1-V7. Thus the presence of these strains in cardiovascular specimens, including heart valve and atheromatous plaque samples extirpated during surgery, and dental plaque samples obtained during oral examination were analysed using the PCR method constructed for this study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 190 cardiovascular specimens (112 from heart valves and 78 from aortic aneurysms), collected from patients who underwent operations at the Department of Cardiovascular Surgery, Osaka Rosai Hospital, Sakai, Osaka, Japan, between December 2004 and July 2007, according to a protocol approved by the Ethics Committee of Osaka Rosai Hospital, and 49 dental plaque specimens collected from patients referred to the Department of Oral Surgery of Osaka Rosai Hospital prior to cardiovascular surgery, were then examined. Bacterial DNA was extracted from each specimen as described previously (Nakano et al, 2006a) and PCR analyses constructed for this study were carried out. The nucleotide alignment of amplified fragments from each positive specimen was confirmed by sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%